IMPACT OF GREEN MANUFACTURING AND INNOVATION ON ORGANIZATION PRODUCTIVITY IN MANUFACTURING COMPANIES - SUBBULAKSHMI, S. (International Journal of Psychosocial Rehabilitation, 2020)
Today’s global awareness about environmental risks and extreme desires to attain global competition were forcing manufacturing systems to transform from traditional system into a new paradigm. In current global scenario, the manufacturing sector needs to protect environment and also increase the organisation productivity in innovative technique. So the corporate is progressively adapting green manufacturing. Green manufacturing is a term used to describe manufacturing practices that do not harm the environment during any part of the manufacturing process. This paper explores the influence of green manufacturing and innovation on organization productivity. Data were collected through questionnaire from manufacturing companies, result were analysed through correlation and regression analysis. The findings revealed that there is positive relationship among green manufacturing and innovation on organisation productivity. Finally, suggests some policy measures to enhance green manufacturing and innovation which leads to greater eco-friendly organization productivity.